Bandwidth Enhancement of a Dual Band Planar Monopole Antenna Using Meandered Microstrip Feeding - M. R. Ahsan; M. T. Islam; M. Habib Ullah; N. Misran (The Scientific World Journal)
A meandered-microstrip fed circular shaped monopole antenna loaded with vertical slots on a high dielectric material substrate (εr=15) is proposed in this paper. The performance criteria of the proposed antenna have been experimentally verified by fabricating a printed prototype. The experimental results show that the proposed antenna has achieved wider bandwidth with satisfactory gain by introducing meandered-microstrip feeding in assistant of partial ground plane. It is observed that, the −10 dB impedance bandwidth of the proposed antenna at lower band is 44.4% (600 MHz–1 GHz) and at upper band is 28% (2.25 GHz–2.95 GHz). The measured maximum gains of −1.18 dBi and 4.87 dBi with maximum radiation efficiencies have been observed at lower band and upper band, respectively. The antenna configuration and parametric study have been carried out with the help of commercially available computer-aided EM simulator, and a good accordance is perceived in between the simulated and measured results. The analysis of performance criteria and almost consistent radiation pattern make the proposed antenna a suitable candidate for UHF RFID, WiMAX, and WLAN applications.